Effects of payments for ecosystem services programs in China on rural household labor allocation and land use: Identifying complex pathways. (December 2020) - Wang, Ying; Zhang, Qi; Bilsborrow, Richard; Tao, Shiqi; Chen, Xiaodong; Sullivan-Wiley, Kira; Huang, Qingfeng; Li, Jiangfeng; Song, Conghe
Highlights: China's core forest PES programs have differential effects on livelihood decisions. PES programs indirectly influence labor allocation and land use via capital assets. Personal attributes have stronger effects on livelihoods than household demographics. Geographic location is also a key determinant of labor allocation and land use. Abstract: Payments for Ecosystem Services (PES) is increasingly used in developing countries to secure the sustainable provision of vital ecosystem services. The largest PES programs in the world are embedded in China's new forest policies, which aim to expand forest cover for soil and water conservation and improve livelihoods of rural people. The objective of this study is to identify the complex pathways of the impacts of two PES programs ,  the Conversion of Cropland to Forest Program (CCFP) and the Ecological Welfare Forest Program (EWFP), on household livelihood decisions, and to quantify the direct and indirect impacts along the identified pathways. We fulfill this objective by developing an integrated conceptual framework and applying a Partial Least Squares-Structural Equation Model (PLS-SEM), based on household survey data from Anhui, China. Labor allocation (for on-farm work, local paid work, local business, or out-migration) and land use decisions (i.e., rent in, maintain, rent out, or abandon cropland) for participating households are key to understand PES program effects on livelihoods. Results show that the PES programs have only small direct effects but significant indirect effects via the mediating factor of capital assets. Moreover, group heterogeneity analysis shows that lower-income households do not benefit more than the better-off households from the PES programs, while households with medium wealth increase dependence on agriculture. In addition, household demographics, individual attributes, and geographic settings differ in their impacts on labor allocation and land use decisions. We conclude that CCFP and EWFP would be more efficient in conserving the environment while improving the economic welfare of lower-income households if capital assets were taken into account in the design of compensation schemes.